PAIN ASSESSMENT AMONGST CHILDREN TREATED WITH DEEP INTRAMUSCULAR INJECTION OF GnRHa IN UMMC - Ambak, Noor Azleen; Sidek, Ruzihan; Alias, Mazni; Tamrin, Noor Fariza Mohammed; Jalaludin, Muhammad Yazid; Samingan, Nurshadia Binti; Leong, Annie; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Trained nurses in our clinic routinely administer deep intramuscular injections of gonadotropin agonist (IM GnRHa). Before the injections, we offer patients options for pain relief prophylaxis. However, we have not regularly assessed the type of pain or the effectiveness of pain relief prophylaxis. METHODOLOGY This cross-sectional study was conducted from January to March 2025, involving all children who received IM GnRHa in the paediatric endocrine clinic at UMMC. The Wong-Baker pain scale, ranging from 0 to 10 (0 indicates no pain and 10 represents the most severe pain), was used to assess pain levels. The pain relief options offered included EMLA cream, ethyl chloride spray, ice packs, or any combination of these methods, based on patient preference. Cases were categorized as follows: New cases involved children who received three injections or less; intermediate cases involved those who received between four and nine injections; and long-term cases comprised those who received ten injections or more. RESULT A total of 80 children received injections during the study period. The majority were female, 73 (91%). The mean age was 10.0 ± 1.41 years. There were 24 (30%) new cases, 24 (30%) intermediate cases, and 32 (40%) chronic or long-term cases. The mean pain scores were 3.37 ± 2.44 for new cases, 3.25 ± 1.62 for intermediate cases, and 2.62 ± 1.64 for chronic/long-term cases. The majority (68 or 85%) of patients chose a combination of EMLA and ethyl chloride spray. Other preferences included the spray alone (8 patients, or 10%), EMLA cream only (3 patients, or 3.75%), and EMLA cream with ice packs (1 patient, or 1.3%). Notably, only two patients in the chronic/long-term category opted for single therapy and reported a higher mean pain score of 5. CONCLUSION We conclude that the more injections the patients received, the less pain they experienced, and that combination prophylaxis appears to be most beneficial. Further randomized studies are needed to determine the best pain relief method for children undergoing deep intramuscular injections in a clinical setting.